Efficient One-Step Separation of Five Flavonoids from the Crude Extract of the Waste Pomace of Sea Buckthorn Berries through Counter-Current Chromatography. (3rd August 2021) - Chen, Tao; Wang, Shuo; Li, Hongmei; Shen, Cheng; Yan, Shuping; Wei, Yangfei; Song, Zhibo; Li, Peipei; Li, Yulin
Abstract: The pomace of sea buckthorn berries is usually discarded when transforming into nonalcoholic or alcoholic beverages, jellies, jams, juices, candies and dairy products. Here, we established a promising approach for one step separation of five flavonoids from the waste pomace of sea buckthorn berries through counter-current chromatography. The crude extract of waste pomace of sea buckthorn berries after juicing was injected into counter-current chromatography with hexane/ethyl acetate/ethanol/water (v/v/v/v, 5:7:5:7) as the solvent system. As a result, five flavonoids, including quercetin, laricitrin, isorhamnetin-7-O-rhamnoside, kaempferol and isorhamnetin, were obtained in a single step separation. Our finding showed that ethanol is a good substitute for methanol to regulate the partition coefficient in hexane/ethyl acetate/ methanol/water system. This study provided a significant measure to utilize the waste pomace of Sea buckthorn berries.